KAJIAN LITERATUR FAKTOR YANG BANYAK MEMPENGARUHI OPINI AUDIT GOING CONCERN - Nish Razak; Rendi Aprianto; Rizka Alfian Rinaldi; Carmel Meiden (Bajang Institute, 2022)
This study aims to summarize the results of previous studies and provide suggestions for further researchers to expand the variables by adding relevant moderating variables to be used in assessing their effect on Going Concern Audit Opinion (GCO). Audit opinion is an important and useful thing for companies that can be used as one of the considerations for creditors or investors to lend some money or to invest. The researcher uses a systematic literature review methodology approach (SLR) with a selected sample of 34 journals published for the period 2006 to 2021. The results show that the factors that have a significant influence on going concern audit opinions are the previous year's audit opinion, debt default, liquidity, auditor reputation and audit lag. Meanwhile, financial distress is a moderating factor for the influence of auditor reputation, auditor switching, and leverage on the acceptance of going concern audit opinions.